The relationship between self-esteem, autonomy and vocational interests - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Sauca (Bors), Filotia (Technium Social Sciences Journal, 2022)
The profession is a complex of theoretical knowledge and practical skills that define one's training. Expectations for a profession are structured around income, safety, satisfaction, assertion, prestige, working conditions and other elements (influence, responsibility, freedom, etc.) (Jurcan, 2005). Forms of educational choice freely and consciously involve a mature student in intellectual, affective-motivational terms. This choice must be made according to the personality characteristics of the students, with talents, abilities, educational interests and values.